2021
DOI: 10.1002/jcph.1947
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on Brexpiprazole Pharmacokinetics: Proposal for Improved Initiation of Treatment

Abstract: Brexpiprazole is an oral antipsychotic agent indicated for use in patients with schizophrenia or as adjunctive treatment for major depressive disorder. As obesity (body mass index ≥35 kg/m 2 ) has the potential to affect drug pharmacokinetics and is a common comorbidity of both schizophrenia and major depressive disorder, it is important to understand changes in brexpiprazole disposition in this population. This study uses a whole-body physiologically based pharmacokinetic model to compare the pharmacokinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…PBPK models can predict PK by incorporating in vitro data, drug and system properties, and drug‐metabolizing enzymes. Bruno et al 40 used a PBPK model to compare the PK of brexpiprazole in obese and normal‐weight individuals known to be CYP2D6 extensive metabolizers (EMs) and poor metabolizers (PMs). Results showed that a dosing strategy of 1 week of twice‐daily dosing in obese EMs or 2 weeks of twice‐daily dosing in obese PMs, followed by a return to once‐daily dosing, yielded more consistent plasma concentrations between obese and normal‐weight patients.…”
Section: Discussionmentioning
confidence: 99%
“…PBPK models can predict PK by incorporating in vitro data, drug and system properties, and drug‐metabolizing enzymes. Bruno et al 40 used a PBPK model to compare the PK of brexpiprazole in obese and normal‐weight individuals known to be CYP2D6 extensive metabolizers (EMs) and poor metabolizers (PMs). Results showed that a dosing strategy of 1 week of twice‐daily dosing in obese EMs or 2 weeks of twice‐daily dosing in obese PMs, followed by a return to once‐daily dosing, yielded more consistent plasma concentrations between obese and normal‐weight patients.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of distribution after intravenous administration is approximately 1.56 ± 0.42 L/kg, which suggests an extravascular distribution. The drug has significant lipophilic properties, which enables the blood–brain barrier transfer, but could also result in storage in fat tissue [ 15 ]. Maximum drug concentration is reached 4 h after oral ingestion, the biological half-life is 91 h [ 16 ].…”
Section: Pharmacological Profile Of Brexipiprazolementioning
confidence: 99%
“…Prolonged half-lives observed in obese individuals may necessitate adjustments to loading dose timing and frequency to achieve the desired therapeutic concentrations efficiently, without leading to overdosing. 54,55 Fixed Dosing. Fixed dosing is a method of drug administration in which the same dose of a medication is prescribed for all patients, regardless of their body weight or size.…”
Section: What Is the Role Of The Therapeutic Window Of A Drug For Inf...mentioning
confidence: 99%
“…PBPK modeling is already used in specific cases to inform labeling surrounding enzyme induction resulting from drugdrug interactions, 82 and to inform dosing regimens in people with obesity. 55 Here, the second example is an instance of low priority for a study, but still requires simulations because although neither the expected average concentrations nor AUCs are expected to change, loading doses are also susceptible to safety or lack-of-efficacy events because of changes in Vd or half-life. Modeling-based approaches can be used here to bridge the gap and inform dosing.…”
Section: Decision Tree To Guide the Prioritization Of Drugs For A Ded...mentioning
confidence: 99%